Synthesis of –CN– linked covalent organic frameworks via the direct condensation of acetals and amines. Issue 45 (19th April 2016) - Li, Zhi-Jun; Ding, San-Yuan; Xue, Hua-Dong; Cao, Wei; Wang, Wei
Abstract : We demonstrate herein a facile approach for constructing –CN– linked COFs from acetals. Abstract : We demonstrate herein a facile approach for constructing –CN– linked COFs from acetals. Three new COFs (imine-linkedLZU-20, hydrazone-linkedLZU-21, and azine-linkedLZU-22 ) were synthesized by the direct condensation of dimethyl acetals and amines. All the synthesized COFs are highly crystalline and exhibit good thermal stability.